PENGARUH WORKPLACE STRETCHING ACTIVE DYNAMIC BACK EXERCISE TERHADAP PENINGKATAN AKTIVITAS FUNGSIONAL LOW BACK PAIN MYOGENIC PADA PENJAHIT - Hesti Sufreshtri; Nurwahida Puspitasari (VISIKES: Jurnal Kesehatan Masyarakat, 2020)
Background: Myogenic low back pain a syndrome that has a broad impact not only for sufferers but also has an impact on the work environment and social so that it can result in disruption of work and decreased work productivity. As many as 30% people aged 30-35 years, 30% people aged 41-45 years, 25% people 36-40 years and 15% people aged 46-50 years old experience low back pain myogenic which can affect the ability of functional activity. One of the treatments of myogenic low back pain is workplace stretching active dynamic back exercise. Objective: The study aims to determine the effect of stretching active dynamic back exercise workplace on increasing functional activity of myogenic low back pain in tailors. Method: The research employed quasi experimental design with pre and posttest one group design. The sampling techniques was purposive sampling. The research samples were tailors aged 30-55 years with a total sample of 20 people consisting of 1 group. The intervention was carried out for 2 weeks. The measurement of functional activities ability used Oswestry disability index (ODI). The data analysis used paired sample t-test. Result: The paired sample t-test obtained p-value = 0.000 (p <0.05), meaning that there was an effect of workplace stretching active dynamic back exercise on increasing functional activity of myogenic low back pain in tailors. Conclusion: There is an effect of workplace stretching active dynamic back exercise on increasing the functional activity of myogenic low back pain in tailors. Suggestion: Further researchers are expected to be able to control the work attitude of the respondents to get more significant result of functional activity changes.Keywords: Workplace Stretching Active Dynamic Back Exercise, Low Back Pain Myogenic, Tailor, Oswestry Disability Index.